Branding dan Pengembangan Olahan Pangan Lokal Lele sebagai Produk Unggulan Umkm Perempuan Kampung Bungaraya Kabupaten Siak - Tantri Puspita Yazid; Ahmad Hadi; Irwan Iskandar; Fiona Fiona; Muhammad Firdaus; Chelsy yesicha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
This community service program was implemented to empower women's groups in Bungaraya Village, Siak Regency, through the development of value-added and competitive processed catfish products. This activity is part of the implementation of the Social Inclusion-Based Library Transformation (TPBIS), which prioritizes libraries as centers for improving literacy and community welfare. The approach used included discussion methods, direct practice, and coaching focused on improving technical skills (making catfish floss and crackers), strengthening branding, utilizing social media and marketplaces as marketing tools, and assistance with business legality. The results of the activity showed that participants experienced significant improvements in their understanding of entrepreneurship, productivity, and creativity in creating new products based on local potential. In addition, this activity also strengthened social relations among participants and increased women's confidence in entrepreneurship. This activity directly supports the achievement of the Sustainable Development Goals (SDGs), specifically goal 5 (gender equality) and goal 8 (inclusive economic growth). With a comprehensive approach, this program has proven effective in building economic independence and strengthening the role of women in community-based village development.